Microwave spectroscopy of the calcium 4snf → 4s(n + 1)d, 4sng, 4snh, 4sni, and 4snk transitions - J. Nunkaew (2018)
© 2015 American Physical Society. We observe the microwave transitions of calcium from the 4snf states to the 4s(n + 1)d, 4sng, 4snh, 4sni, and 4snk states for 18 ≤ n ≤ 23 using delayed field ionization as the state selective detection technique. The observed intervals between the ℓ ≥ 5 states can be analyzed to extract the Ca < sup > + < /sup > ionic dipole (α < inf > d < /inf > ) and quadrupole (α < inf > q < /inf > ) polarizabilities using two nonadiabatic core polarization models. Using these two models we determine the ionic dipole and quadrupole polarizabilities to be 75.3a < inf > 0 < /inf > < sup > 3 < /sup > < α < inf > d < /inf > < 76.9a < inf > 0 < /inf > < sup > 3 < /sup > and 206a < inf > 0 < /inf > < sup > 5 < /sup > < α < inf > q < /inf > < 1590a < inf > 0 < /inf > < sup > 5 < /sup > , respectively.